Ethical Leadership, Organizational Citizenship Behavior, and Nurses' Job Performance: The Moderating Role of Job Satisfaction - Asrida (PT PUSTAKA CENDEKIA GROUP, 2025)
This study aims to analyze the influence of ethical leadership on nurse performance by placing organizational citizenship behavior as a mediator variable and job satisfaction as a moderator variable. Using a quantitative approach with an explanatory design, this study involved nurses in Kendari City as respondents. Data was collected through a structured survey and analyzed using Structural Equation Modeling technique based on Partial Least Squares. The results of the study revealed that ethical leadership is a significant driving factor in improving nurses' performance directly and through improving voluntary behavior in the work environment. In addition, organizational civic behavior has proven to be a crucial element that is independently able to increase the effectiveness of nurse performance. Important findings in this study suggest that job satisfaction plays a role as a catalyst that amplifies the positive impact of voluntary behavior on performance; This means that nurses who are willing to work beyond their formal duties will produce much more optimal performance if supported by a high level of job satisfaction. Overall, this study concludes that strengthening the integrity of leaders and creating a satisfactory work environment are key strategies in optimizing the professional contribution of nurses in Kendari City.